Prognostic Significance of Neutrophil to Lymphocyte Ratio in Patient with NonMuscle Invasive Bladder Cancer Who Underwent Intravesical BCG Treatment - Mohamed Ibrahim Elmoazen; Amr Elshorbagy; Amr Elshorbagy; Mohamed Maher Mohamed; Mohamed Maher Mohamed; Ahmed Emam (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Urinary bladder cancer (BC) is the ninth most common cancer in the world and the 13th cause of cancer deaths. Aim of work: The aim of our study was to assess the role of pretreatment neutrophil-to- lymphocyte ratio (NLR) as a predictor of clinical outcomes in patients with non-muscle invasive bladder cancer (NMIBC) who underwent intravesical Bacillus Calmette-Guérin (BCG) treatment. Methods: This retrospective study was conducted at Ain-shams university hospital and included 100 patients having NMIBC. Results: NLR can predict recurrence at further follow up cystoscopy at cutoff 3.3 with sensitivity of 89.7%, specificity of 85.2%, PPV of 79.5%, NPV of 92.9% and AUC was 0.90. Conclusions: Our data showed that a high value of NLR (add cutoff) evaluated preoperatively might be helpful to predict the BCG response and therefore provide critical information for the clinical management of high-risk NMIBC patients together with the prognostic factors already known.